2006
DOI: 10.1116/1.2219759
|View full text |Cite
|
Sign up to set email alerts
|

Previous heat treatment inducing different plasma nitriding behaviors in martensitic stainless steels

Abstract: In this work we report a study of the induced changes in structure and corrosion behavior of martensitic stainless steels nitrided by plasma immersion ion implantation (PI3) at different previous heat treatments. The samples were characterized by x-ray diffraction and glancing angle x-ray diffraction, scanning electron microscopy, energy dispersive x-ray spectroscopy, and potentiodynamic measurements. Depending on the proportion of retained austenite in the unimplanted material, different phase transformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The effect of previous heat treatment was reported by Figueroa et al [86]. AISI 420 martensitic stainless samples were quenched and tempered at two different temperatures, 310 and 530 • C, for 1 h, and then they were PIII nitrided in the range of 340-500 • C. It was observed that the tempering temperature influenced the volume fraction of retained austenite, and that this phase, in turn, influenced the phases which formed during nitriding.…”
Section: Formation Of Expanded Martensitementioning
confidence: 73%
“…The effect of previous heat treatment was reported by Figueroa et al [86]. AISI 420 martensitic stainless samples were quenched and tempered at two different temperatures, 310 and 530 • C, for 1 h, and then they were PIII nitrided in the range of 340-500 • C. It was observed that the tempering temperature influenced the volume fraction of retained austenite, and that this phase, in turn, influenced the phases which formed during nitriding.…”
Section: Formation Of Expanded Martensitementioning
confidence: 73%
“…Thus, in [ 18 ], the induced changes in the structure and corrosion resistance of martensitic stainless steels nitrided by plasma-immersion ion implantation during various previous heat treatments were investigated. In [ 19 ], the results of experimental and analytical studies of ignition modes of a low-pressure discharge in nitrogen with the simultaneous application of constant and high-frequency (HF) electric fields are presented.…”
Section: Introductionmentioning
confidence: 99%
“…However, for severe surface working conditions, its hardness and wear resistance must be improved [10][11][12]15]. To overcome this limitation, plasma assisted nitriding has been successfully applied [7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25]. In the last decades, studies were conducted aiming to improve martensitic stainless steels wear and corrosion resistance by applying plasma assisted technology [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, martensitic stainless steels present metastable structure and, as such, require careful choice of treatment conditions to avoid undesirable phase transformation during nitriding. On the other hand, if the process is carried out at lowtemperatures, typically below 400˚C, the chromium nitride precipitation is avoided, and wear and corrosion resistance of the treated stainless steel surface is enhanced [18][19][20][21][22][23]. For low-temperature nitrided martensitic stainless steels, iron nitrides and a supersaturated phase, termed as nitrogen-expanded martensite, have been regularly obtained [8][9][10][11][12]18,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation